APLIKASI MONITORING MANAJEMEN OPERASIONAL PERKEBUNAN SAWIT BERBASIS WEB - Nur Laila; Ahmad Akbar; Chairul Rizal (CV. Hawari, 2025)
The oil palm plantation sector in Indonesia faces significant operational efficiency challenges due to manual record-keeping, limited field activity monitoring, and suboptimal resource management, potentially leading to decreased yields and productivity. This research aims to develop a